Innovative financing to fund surgical systems and expand surgical care in low-income and middle-income countries - Rifat Atun; Alexander W Peters; Luke Caddell; John G Meara; Ché L Reddy; Desmond Tanko Jumbam; Blake C Alkire (BMJ Global Health)
Strong surgical systems are necessary to prevent premature death and avoidable disability from surgical conditions. The epidemiological transition, which has led to a rising burden of non-communicable diseases and injuries worldwide, will increase the demand for surgical assessment and care as a definitive healthcare intervention. Yet, 5 billion people lack access to timely, affordable and safe surgical and anaesthesia care, with the unmet demand affecting predominantly low-income and middle-income countries (LMICs). Rapid surgical care scale-up is required in LMICs to strengthen health system capabilities, but adequate financing for this expansion is lacking. This article explores the critical role of innovative financing in scaling up surgical care in LMICs. We locate surgical system financing by using a modified fiscal space analysis. Through an analysis of published studies and case studies on recent trends in the financing of global health systems, we provide a conceptual framework that could assist policy-makers in health systems to develop innovative financing strategies to mobilise additional investments for scale-up of surgical care in LMICs. This is the first time such an analysis has been applied to the funding of surgical care. Innovative financing in global surgery is an untapped potential funding source for expanding fiscal space for health systems and financing scale-up of surgical care in LMICs.